Nanoenviroments of the β-Subunit of L-Type Voltage-Gated Calcium Channels in Adult Cardiomyocytes - Cruz-Garcia, Yiliam; Barkovits, Katalin; Kohlhaas, Michael; Pickel, Simone; Gulentz, Michelle; Heindl, Cornelia; Pfeiffer, Kathy; Eder-Negrin, Petra; Maack, Christoph; Marcus, Katrin; Kuhn, Michaela; Miranda-Laferte, Erick (Frontiers in Cell and Developmental Biology, 2022)
In cardiomyocytes, Ca2+ influx through L-type voltage-gated calcium channels (LTCCs) following membrane depolarization regulates crucial Ca2+-dependent processes including duration and amplitude of the action potentials and excitation-contraction coupling. LTCCs are heteromultimeric proteins composed of the Cavα1, Cavβ, Cavα2δ and Cavγ subunits. Here, using ascorbate peroxidase (APEX2)-mediated proximity labeling and quantitative proteomics, we identified 61 proteins in the nanoenvironments of Cavβ2 in cardiomyocytes. These proteins are involved in diverse cellular functions such as cellular trafficking, cardiac contraction, sarcomere organization and excitation-contraction coupling. Moreover, pull-down assays and co-immunoprecipitation analyses revealed that Cavβ2 interacts with the ryanodine receptor 2 (RyR2) in adult cardiomyocytes, probably coupling LTCCs and the RyR2 into a supramolecular complex at the dyads. This interaction is mediated by the Src-homology 3 domain of Cavβ2 and is necessary for an effective pacing frequency-dependent increase of the Ca2+-induced Ca2+ release mechanism in cardiomyocytes.